2021
DOI: 10.1097/ju.0000000000001694
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride Use and Risk of Bladder Cancer in a Multiethnic Population

Abstract: Purpose: Finasteride use has been associated with a reduced incidence of bladder cancer. However, the majority of studies have been conducted primarily in East Asian or White populations. Given differences in the incidence of bladder cancer among racial/ethnic groups, it is important to determine whether the effect of finasteride use on bladder cancer varies by race/ethnicity. Materials and Methods: We identified all patients with a diagnosis of benign prostatic hyperplasia between 2000 and 2016 at our academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Overall, according to the screening criteria, the systematic review and meta-analysis included 18 studies with a total of 414 007 male patients ( 21 38 ) ( Figure 1 ). Eight studies evaluated the effect of AST on bladder cancer incidence ( 22 , 27 , 28 , 30 , 32 34 , 38 ). Ten studies examined the effect of AST on bladder cancer recurrence, progression and survival ( 21 , 23 26 , 29 , 31 , 35 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, according to the screening criteria, the systematic review and meta-analysis included 18 studies with a total of 414 007 male patients ( 21 38 ) ( Figure 1 ). Eight studies evaluated the effect of AST on bladder cancer incidence ( 22 , 27 , 28 , 30 , 32 34 , 38 ). Ten studies examined the effect of AST on bladder cancer recurrence, progression and survival ( 21 , 23 26 , 29 , 31 , 35 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al. ( 38 ) indicated that the use of finasteride was associated with significant reductions in the risk of high-grade BCa and non-muscle invasive BCa. In addition, a decrease in the risk of BCa was shown only in Caucasians and Hispanics but not among African Americans.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations